BUDGET’S UNIQUE ROLE IN POVERTY PROBLEM SOLVING IN UKRAINE - Kyrylenko, Ol’ga; Bilous, Iryna (Journal of European Economy, 2017)
Budget expenditures aimed at poverty solving of Ukrainians are investigated. Budget’s role in solving poverty problem is explored; ways of budget expenditures improvement connected with most vulnerable and poor groups of society are demonstrated.